2018
DOI: 10.3390/catal8120575
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Methylene Blue over TiO2 Pretreated with Varying Concentrations of NaOH

Abstract: In this paper, different NaOH concentrations (2, 5, 10, and 15 M) were used to treat {001}TiO2. The effect of NaOH on the crystal structure, morphology, optical properties, light raw electronic-hole recombination, and degradation performance of {001}TiO2 on methylene blue were studied. The results demonstrate that rutile TiO2 appeared when the NaOH concentration was as high as 10 M, showing much better photolytic performance than others. As the concentration of sodium hydroxide increases, the morphology change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(58 citation statements)
references
References 48 publications
5
51
1
1
Order By: Relevance
“…It manifests by a linear trend of the concentration-time data plot (Figure 8). Contrary, the decrease of MB concentration has exponential character, (Figure 9), similar to those visible in the literature [69,70]. It forces the application of two different approaches to experimental data.…”
Section: Discussionsupporting
confidence: 78%
“…It manifests by a linear trend of the concentration-time data plot (Figure 8). Contrary, the decrease of MB concentration has exponential character, (Figure 9), similar to those visible in the literature [69,70]. It forces the application of two different approaches to experimental data.…”
Section: Discussionsupporting
confidence: 78%
“…In the process of adding glucose drop by drop, the concentration of NaOH was also decreasing gradually. It was found that NaOH and (001)TiO 2 not only increased the content of (001) facets, but also changed the morphology of the catalysts, which was consistent with the results of Hou et al [47]. CuSO + 2NaOH = Cu(OH) + Na SO ↓…”
Section: Raman Analysis Of Catalystssupporting
confidence: 89%
“…The XRD pattern of the sample is shown in Fig. 2 16 . Therefore, it can be seen that Cu and Ti have been successfully compounded.…”
Section: Characterization Resultsmentioning
confidence: 99%
“…TiO 2 has good chemical and biological stability, but it has become a bottleneck for development due to its low light utilization and fast photocarriers recombination. [16][17][18][19] To change this situation, many studies have enhanced the response of TiO 2 in the visible region by doping TiO 2 with non-metals (C, N, F, S, etc.) 2,[20][21][22] and semiconductors (Cu 2 O, CdS, etc.).…”
Section: Introductionmentioning
confidence: 99%